2017
DOI: 10.1080/15384101.2017.1380135
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of co-expression networks for circular RNAs and mRNAs reveals that circular RNAs hsa_circ_0047905, hsa_circ_0138960 and has-circRNA7690-15 are candidate oncogenes in gastric cancer

Abstract: Accumulating evidence has suggested that circular RNAs (circRNAs) play important roles in oncogenesis and tumor progression. However, our knowledge of circRNAs in gastric cancer (GC) remains limited. To investigate circRNAs involved in GC oncogenesis, we examined differentially-expressed circRNAs and mRNAs in GC tissues and paired noncancerous mucosa tissues using circRNA and mRNA microarrays. Next, we built gene co-expression networks according to the degree of correlation to predict the critical circRNAs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…In addition, circRNA_001569 overexpression promoted cell viability and decreased GC apoptosis by suppressing miR-145 expression, which is mediated by NR4A2 [18]. Furthermore, inhibition of 3 circRNAs (circRNA0047905, circRNA0138960 and circRNA7690-15) restrained the cell invasion and proliferation of GC in vitro [19]. Future research should focus on the mechanism of action of these newly discovered circRNAs in GC.…”
Section: Circrnas That Act As Oncogenes In Gcmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, circRNA_001569 overexpression promoted cell viability and decreased GC apoptosis by suppressing miR-145 expression, which is mediated by NR4A2 [18]. Furthermore, inhibition of 3 circRNAs (circRNA0047905, circRNA0138960 and circRNA7690-15) restrained the cell invasion and proliferation of GC in vitro [19]. Future research should focus on the mechanism of action of these newly discovered circRNAs in GC.…”
Section: Circrnas That Act As Oncogenes In Gcmentioning
confidence: 98%
“…With the continuous improvement of high-throughput sequencing technology and bioinformatics, abundant and diverse circRNAs have been identified in various developmental stages and physiological conditions in numerous organisms, including humans [13], mice [13], and monkeys [14]. Many reports have revealed that circRNAs are indispensable in various physiological and pathological processes [15][16][17][18][19]. Recently, multiple possible biological functions of circRNAs have been discovered ( Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Lai et al examined co-expression networks between circRNAs and mRNAs and found three candidate (circRNA0047905, circRNA0138960 and circRNA7690-15) oncogenes in gastric tissue. circRNA0047905 was predicted as biomarker in gastric tissue as it showed highest diagnostic accuracy [164]. Huang et al analyzed plasma samples from patients with GC and healthy controls and showed hsa_circ_0000745 to be downregulated in GC tissue.…”
Section: Gastric Cancermentioning
confidence: 99%
“…Due to their considerable stability, CircRNAs and their role in cancer have been the focus of extensive research in recent years as potential tumor molecular targets [15][16][17], especially in GC [18]. Some researchers have observed that circ_002059, circ_0000745, circ_00000181, circ_0047905, circ_0014717, circ_0001017, and circ_0061276 were signi cantly downregulated in patients with GC, and have better sensitivity and speci city for the diagnosis of GC [19][20][21][22][23][24]. Additionally, the role of microRNAs has been highlighted in the development and maintenance of drug resistance in GC, which is the most vital cause of GC treatment failure.…”
Section: Introductionmentioning
confidence: 99%